Pelaksanaan Diversi Terhadap Anak Sebagai Pelaku Tindak Pidana Kecelakaan Lalu Lintas Di Kepolisian Resor Gianyar - I Gusti Ayu Claudia Prathami Mertha; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Fakultas Hukum Universitas Warmadewa, 2019)
The traffic accident incident involving the Yamaha V-Ixion DK 2245 LP motorbike was driven by the suspect I Wayan Sudita aged 15 (fifteen) years hit a pedestrian on behalf of I Ketut Lana while crossing the road, the accident occurred because of a lack of caution the bicycle driver The Yamaha V-Ixion DK 2245 LP motorbike while driving its vehicle coming from the south to the north after arriving at the crime scene does not give priority to pedestrians crossing the road from the west to the east of the road so that accidents result in pedestrians being injured and subsequently died at Sanjiwani General Hospital, Gianyar. The formulation of the problem in this study is: how is the implementation of diversion by investigators against children as perpetrators of crimes in the Gianyar Resort Police and what are the inhibiting factors in the implementation of diversion in the Gianyar Resort Police. The type of research used is empirical research. Based on these discussions the results of this study are as follows: The implementation of diversion by investigators in handling child cases at Gianyar Resort, carried out by presenting perpetrators, victims, families of perpetrators and victims, correctional guides, community leaders, and related parties. Before conducting diversion, the investigator first conducts an interview with the perpetrator to understand the motive of the perpetrator to commit the crime, so that the investigator is easier to seek diversion to reach an agreement. The inhibiting factor in implementing diversion in the Gianyar Resort Police is the lack of cross-sectoral coordination between the Gianyar Resort Police and the Social Service, Tinas Tenaga Kerja, Women's Empowerment and Family Planning Agency in Gianyar Regency.